Analisis Tingkat Kepatuhan Wajib Pajak Bumi dan Bangunan Dalam Meningkatkan PAD Kota Medan : Penelitian - Yohana Michelle Kaban; Junawan; Tengku Eka Susilawaty (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the compliance level of Land and Building Tax (PBB) taxpayers in enhancing local revenue (PAD) at the Regional Revenue Agency (Bapenda) of Medan City from 2020 to 2024. A descriptive method with a quantitative approach was employed by collecting and presenting relevant data. Data were gathered through interviews and documentation, including taxpayer compliance rates, records of registered and active taxpayers, and realization data of PBB and PAD revenues. The results indicate that the compliance level of PBB taxpayers in Medan City remains fluctuating and has not reached an optimal level, although the contribution of PBB to PAD has been relatively significant each year. These findings suggest that taxpayer compliance plays a critical role in supporting PAD revenues, while also highlighting the need for strategies to improve compliance through enhanced public services, effective outreach, and incentive-based tax policies.